2021 European Conference on Optical Communication (ECOC) 2021
DOI: 10.1109/ecoc52684.2021.9605988
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of 8-Dimensional Voronoi Constellations with 65,536 and 16,777,216 Symbols

Abstract: We experimentally demonstrate high-cardinality, low-complexity Voronoi constellations based on the E8 lattice over multiple time slots with OSNR and launch power gains of up to 1.7 and 2.4 dB for back-to-back and 80 km fiber transmission, respectively, compared to QAM formats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In general, standard DSP algorithms designed for QAM work for VCs as well without modification. In [20], a pilot-based DSP algorithm described in [33] has been used for transmission of VCs in experiments.…”
Section: Performance Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In general, standard DSP algorithms designed for QAM work for VCs as well without modification. In [20], a pilot-based DSP algorithm described in [33] has been used for transmission of VCs in experiments.…”
Section: Performance Analysismentioning
confidence: 99%
“…VCs were first studied for fiber communications in [18], where Mirani et al reported significant uncoded bit error rate (BER) gains of VCs over QAM transmitted in a wavelengthdivision multiplexing (WDM) system. Later in [20], power gains of VCs were demonstrated in experiments for a 80 km single-channel transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties make VCs a suitable option for applications with strict limits on latency or power consumption, e.g., video conferencing or instrument control links that are latency sensitive [25]. The VCs have been realized in optical communication systems at 8 dimensions over time slots [27] and 32 dimensions over multiple wavelengths, polarizations and time slots [28]. Another type of VCs based on cubic coding lattice is investigated in [29] for single and multi-wavelength transmission simulations and mutual information (MI), generalized mutual information (GMI), and bit-error rate (BER) metrics are compared with quadrature amplitude modulation (QAM) formats.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, which is an extension of [27] and [28], we investigate different realizations of VCs in 8, 16, and 32 dimensions and compare their BER performance both in simulation and experiment in back-to-back (B2B) and long-haul fiber transmission. We show up to 22 and 70% transmission reach improvement for VCs compared to 4QAM and 16QAM at the hard-decision forward error correction (HD-FEC) limit, respectively.…”
Section: Introductionmentioning
confidence: 99%